Penerapan Metode Peer Teaching Dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Dan Budi Pekerti Kelas XII IPS3 SMA Negeri 1 Besitang - Lisa Mahdalena Br Sitepu; Nanda Rahayuu Agustia (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study looks at the use of peer learning techniques as a substitute to boost students' passion for learning, which is seen to be doable in a classroom setting. This study aims to investigate how well peer learning techniques might boost students' enthusiasm to learn in Islamic Religious Education and Character Education classes in class XII IPS 3 SMA Negeri 1 Besitang. This research employs a case study design and a descriptive qualitative methodology. Direct observation, document collection, and interviews were used as data collection methods. The interactive model of Miles and Huberman, which comprises the steps of data filtering, information display, and conclusion formulation, served as the basis for the data analysis. The results of the study show that using peer learning strategies helps students become more motivated to learn. By using this method, students become more actively involved in the learning process, which makes it more dynamic, dialogical, and critical thinking-oriented.